(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Since its nationalisation, the banking industry has been an integral part of the country’s economic growth. As a result of globalisation, international banks have been giving India’s banks a run for their money. Looking mostly at public and private banks, this article aims to forecast the future of retail portfolio management based on financial performance. Both primary and secondary sources of information were used to conduct the study. One area of the service economy that has seen radical transformation is the banking industry, which has evolved at a dizzying rate to meet the demands of modern international trade. The Government of India has complete authority over the banking sector in India according to its code.